Tympanostomy tubes in the age of quarantine. (March 2022) - Pereira, Nicola M.; Maresh, Alison M.; Modi, Vikash K.; Rosenblatt, Steven D.
Abstract: Objectives: After state-mandated COVID-19 quarantine measures were lifted in 2020, pediatric otolaryngologists noticed that many children who were previously scheduled for tympanostomy tube (TT) placement for indications of acute otitis media (AOM) or chronic middle ear effusions (OME) no longer required surgery. This study aims to describe the effect of home-quarantine on pediatric patients with recurrent AOM and OME to increase our understanding of these conditions. Methods: This was a retrospective review of pediatric patients that were originally scheduled for TT for recurrent AOM and/or OME, but had their procedure cancelled due to COVID-19. The chi-square test was used to compare the proportion of patients who no longer met indications for surgery stratified by original indication. Data was also collected for TT volume in the months before and after the start of the pandemic. Results: Of 59 patients originally scheduled for TT, 31.0% of the 42 patients who returned for follow-up still met indications for a procedure after a period of home-quarantine. Of these, 76.9% had persistent OME, 61.5% had recurrent AOM, and 69.2% had persistent conductive hearing loss. After elective surgery resumed, there was a substantial decrease in the number of TT procedures performed compared to pre-pandemic data. Conclusion: After a period of quarantine, many patients previously scheduled for TT experienced resolution of their AOM or OME. Despite a nationwide recovery in outpatient surgical volume across otolaryngology practices, TT volumes remain low one year after the start of the pandemic, suggesting that continued COVID-19 precautionary measures are contributing to this lingering effect. Highlights: Home quarantine is associated with resolution of otitis media symptoms in children. Tympanostomy tube volumes decreased in March 2020 and continue to remain low. Continued COVID-19 precautionary measures likely contribute to this lasting effect.